Осврт за процесот на усвојување на државните симболи на Република Македонија во 1992 година - Review of the Process of Adoption of the State Symbols of the Republic of Macedonia in 1992 - Jonovski, Jovan (Македонски хералд - Macedonian Herald, 2019)
The process for determining the coat of arms, the flag, and the anthem. actually started with public competition for the selection of their content/design. Proposals for a law were then presented, followed by a series of amendments by the MPs to the design of the coat of arms and the flag, with the anthem remaining unchanged. The three best entries from the public competition for the coat of arms and flag did not find themselves in the further procedure, but the concept of a coat of arms and a flag with a new design of the sun was introduced. In the whole proess, for a flag, out of six types of proposals, three used the sun, two used a lion, and one used the existing coat of arms. Out of 23 proposals for the coat of arms, there were 16 types of arms—half with a lion and half with a sun. In the end, the greatest support was for the concept of a flag and a coat of arms with a 16-rayed sun, suggested by Todor Petrov. The flag was voted on, but for the arms no concensus was reached.